2017
DOI: 10.1016/j.jecp.2016.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Humor and preschoolers’ trust: Sensitivity to changing intentions

Abstract: This research demonstrates that preschoolers (a) avoid trusting informants with humorous intentions when learning novel information and (b) flexibly consider current intentions rather than initial intentions when determining who to trust. In Study 1 (N=61), 3- and 4-year-olds based their trust on intentions or intentional cues alone, trusting a sincere informant over a joker, even when no prior accuracy or inaccuracy was displayed. In Study 2 (N=32), 3- and 4-year-olds flexibly based their trust on the informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…A fascinating series of studies by Hoicka and her colleagues (Hoicka and Gattis, 2008;Hoicka and Wang, 2011;Hoicka, 2016) shows how toddlers are able to use contextual non-verbal cues (notably laughter) to guide their appraisal of ambiguous events and discriminate between mistakes and jokes from the second year of life (18-24 months). These studies support the idea that humour might be one of the first forms of pragmatically rich meaning young children are exposed to, as well as the most accessible (Hoicka et al, 2017). Therefore, as proposed by Reddy (1991Reddy ( , 2001, the understanding of humorous intentions could be the first step in understanding that someone might want to do the wrong thing, the basis for bootstrapping the successive abilities to understand pretence (Rakoczy et al, 2004), deception (Sullivan et al, 1995), and other forms of pragmatically rich meaning (such as metaphors (Pouscoulous, 2014) and irony (Filippova, 2014)).…”
Section: Laughter As a Sign Of Social Mastery Cultural Attunement And...supporting
confidence: 79%
“…A fascinating series of studies by Hoicka and her colleagues (Hoicka and Gattis, 2008;Hoicka and Wang, 2011;Hoicka, 2016) shows how toddlers are able to use contextual non-verbal cues (notably laughter) to guide their appraisal of ambiguous events and discriminate between mistakes and jokes from the second year of life (18-24 months). These studies support the idea that humour might be one of the first forms of pragmatically rich meaning young children are exposed to, as well as the most accessible (Hoicka et al, 2017). Therefore, as proposed by Reddy (1991Reddy ( , 2001, the understanding of humorous intentions could be the first step in understanding that someone might want to do the wrong thing, the basis for bootstrapping the successive abilities to understand pretence (Rakoczy et al, 2004), deception (Sullivan et al, 1995), and other forms of pragmatically rich meaning (such as metaphors (Pouscoulous, 2014) and irony (Filippova, 2014)).…”
Section: Laughter As a Sign Of Social Mastery Cultural Attunement And...supporting
confidence: 79%
“…A third possibility is that the lab task did not adequately capture humor. However, past research indicates infants and toddlers show an understanding of humor in the lab (Hoicka & Akhtar, 2011 ; Hoicka et al, 2017 ; Hoicka & Gattis, 2008 ; Hoicka & Wang, 2011 ; Mireault et al, 2014 ; Mireault et al, 2015 ). Furthermore, we found that children laughed, and reproduced acts while smiling or laughing, more during joke trials than control trials, suggesting it worked well as a humor experiment at the group level, but perhaps not on an individual differences level.…”
Section: Discussionmentioning
confidence: 99%
“…While early humor research shows some overall patterns of humor development, the list of humor types covered is not exhaustive, and generally covers small age ranges (Addyman & Addyman, 2013 ; Dubois et al, 1984 ; Hoicka & Akhtar, 2012 ; Johnson & Mervis, 1997 ; Loizou, 2004 , 2005 ; Mireault, Poutre, et al, 2012 ; Reddy, 2001 ; Sroufe & Wunsch, 1972 ). Additionally, while children responding to different types of humor within experiments gives us some empirical evidence about humor understanding at different ages (Esseily et al, 2016 ; Hoicka & Akhtar, 2011 ; Hoicka et al, 2017 ; Hoicka & Gattis, 2008 ; Hoicka & Martin, 2016 ; Hoicka & Wang, 2011 ; Mireault et al, 2014 ; Mireault et al, 2015 ; Mireault et al, 2018 ; Shultz, 1976 ; Sroufe & Wunsch, 1972 ; Waters et al, 1975 ), we do not know the extent to which these types of humor are enjoyed in everyday life. What is missing is: (1) a global measure of early humor development; and (2) a systematic taxonomy of humor development in the first years of life.…”
mentioning
confidence: 99%
“…Researchers have sought to understand the ways in which nonepistemic cues can impact selective social learning decisions in children, and a number of informant-based characteristics have been identified. For example, children prefer to learn from informants who are more dominant (Bernard et al, 2016), more honest (Lane et al, 2013;Li et al, 2014), non-obese and physically abled (Jaffer & Ma, 2015), sincere (Hoicka et al,, 2017), dressed more nicely (McDonald & Ma, 2015), and benevolent (Nguyen et al, 2016). Moreover, children opt to learn from informants who are more familiar (though this varies with attachment style; , more helpful (Palmquist et al, 2016), more confident (Birch et al, 2009), and who display greater positive emotionality (Tang et al, 2018).…”
Section: Associated Factorsmentioning
confidence: 99%